Mobile-Assisted Language Learning through Interaction Applications: Analysis and Evaluation - Alexiadou, Eleftheria; Sougari, Areti-Maria (Language, Technology, and Social Media, 2025)
Mobile-Assisted Language Learning (MALL) has become an integral component of contemporary language education, leveraging the ubiquity of mobile technologies to facilitate interactive learning beyond traditional settings. This study critically analyzes and classifies free, texting-based interaction applications, specifically HelloTalk and Linguado, assessing their features, pedagogical effectiveness, and user experiences through a mixed-methods design. Data were collected from twelve adult learners using judgmental evaluations, structured questionnaires, and semi-structured interviews. Results demonstrate that HelloTalk exhibits superior feature diversity, user engagement, and facilitation of cultural exchange compared to Linguado, positioning it as more effective for intermediate language learners. Nonetheless, both applications present challenges concerning user safety, technical stability, and informal learning constraints. The study contextualizes these findings within constructivist and communicative language teaching frameworks, underscoring the potential of interaction applications to enhance communicative competence and intercultural understanding. Recommendations include advancing user safety protocols and integrating sophisticated interactive elements such as AI-driven chatbots to augment pedagogical value. This research addresses critical gaps in MALL application evaluation, particularly for adult learners and non-English languages, contributing valuable insights for educators, developers, and policymakers in digital language education.